2016
DOI: 10.1530/eje-16-0193
|View full text |Cite
|
Sign up to set email alerts
|

DIAGNOSIS OF ENDOCRINE DISEASE: How reliable are free thyroid and total T3 hormone assays?

Abstract: Hypothyroidism is a very common disorder worldwide, for which the usual treatment is monotherapy with levothyroxine (L-T4). However, a number of patients treated with L-T4 continue to report symptoms of hypothyroidism despite seemingly normal levels of thyroid stimulating hormone (TSH), free-T3 (FT3), and free-T4 (FT4) measured by immunoassay. This review summarizes the limitations of the immunoassays commonly used to measure thyroid hormones and emphasizes the advantages of the role of liquid chromatography-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 59 publications
1
72
0
Order By: Relevance
“…Limitations of this study include the specialized patient population with multiple transplant patients. Nonetheless, the results of this investigation contribute to the multiple studies (reviewed in (4, 5)) highlighting inaccuracies with common immunoassay platforms in several patient populations.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Limitations of this study include the specialized patient population with multiple transplant patients. Nonetheless, the results of this investigation contribute to the multiple studies (reviewed in (4, 5)) highlighting inaccuracies with common immunoassay platforms in several patient populations.…”
Section: Discussionmentioning
confidence: 89%
“…However, a number of studies have shown discrepancies in free and total thyroid hormone measurement by immunoassay when compared to a reference method such as liquid chromatography-tandem mass spectrometry (LC-MSMS) in several populations (reviewed in (4, 5)). Multiple studies have shown falsely normal values for TT3, FT, and FT4 by immunoassays that are below the reference interval when measured by reference LC-MSMS in a number of patient populations (3, 68).…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard for measurement of free thyroid hormones (fT 3 and fT 4 ) is a method involving a separation step of bound from free thyroid hormone, classically a dialysis method ( 62 ) or recently the LC/MS method; but none of these methods are widely available. In our study, free thyroid hormones were measured by an immunoassay.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, free thyroid hormones were measured by an immunoassay. Immunoassays can both overestimate and underestimate free thyroid hormone concentrations depending on the platform used for the assay ( 62 ). However, there is no reason to suspect that a potential overestimation of free T 3 and free T 4 serum concentrations should be biased in relation to the exposure to UV filters and thereby might not have affected the results.…”
Section: Discussionmentioning
confidence: 99%
“…However, various practical and technical issues related to above-mentioned challenges of TH physiology and pathophysiology hampered rapid progress and success in quantification of total and free THM concentrations. While meanwhile several laboratories developed procedures to accurately determine total T4 and total T3 in human plasma or serum and largely agree on concentrations ranges (25,(67)(68)(69)(70)(71)(72)(73), this consensus has not been achieved yet for most of the other TH metabolites, which occur at much lower concentrations. Analytical procedures typically work well with buffer solutions, in vitro reaction mixtures, as well as with samples of "simple" matrix composition, while reported concentrations in human or experimental animal serum, plasma, and tissue show wide variations and marked insufficiencies in terms of method validation, standardization, and quality assessment parameters [see (23,24,74)].…”
Section: Alternative Lc-ms-based Approaches Are Needed To Determine Cmentioning
confidence: 99%